STATIC ANALYSIS OF THE HYDRAULIC FRONT-WHEEL DRIVE SYSTEM OF A UNIVERSAL WHEELED TRACTOR - B. J. Astanov; H. O. Meliyev (Web of Journals Publishing, 2025)
This article presents the results of a static analysis of the hydraulic front-wheel drive system of a universal wheeled tractor. The study focuses on evaluating the balance of forces and moments acting on the front drive assembly under stationary conditions. The methodology includes determining the required hydraulic pressure and flow rate to ensure the stable operation of the front drive mechanism. Key structural parameters of the system, such as cylinder diameter, piston stroke, and mounting geometry, are considered in the calculation. The outcomes of the analysis provide essential data for improving the operational efficiency, reliability, and load-bearing capacity of front-wheel drive systems in agricultural machinery.
Keywords: Hydraulic system, front-wheel drive, universal tractor, static analysis, cylinder force, agricultural machinery, drive mechanism, load distribution, design parameters.